An emulation of VoD services using virtual network environments - Fuertes, Walter; López de Vergara M., Jorge (Electronic Communications of the EASST, 2009)
Virtualization platforms are a viable alternative for the implementation of IP network experimentation environments. These platforms facilitate the conducting of tests as if a real environment were used and therefore can reduce the risk of failure as well as investment and experimentation costs. This paper proposes to develop a method to improve the results obtained in virtual network environments, trying to resemble those obtained in a real environment. To carry this out, we have emulated a video-on-demand service over ADSL using Xen as a virtualization tool, just as it would have been through a real ADSL connection. Connectivity, IP addressing, switching, routing and video streaming were tested to check the functionality of virtual network environments. Then, the bandwidth, the delay, and the inter-arrival time of video streaming packets were measured both in real and virtual environments. Finally, these parameters were tuned in the virtual network environments obtaining a similar behavior in clients and servers of both cases.